Regional Determinants of MNE's Location Choice in Transition Economies - Andrea Gauselmann; Philipp Marek (Austrian Institute of Economic Research (WIFO), 2011)
This paper analyses the impact of agglomeration effects, labour market conditions and other determinants on the location choice of MNEs in transition economies. We compare data from 33 regions in East Germany, the Czech Republic and Poland using a conditional logit model on a sample of 4,343 subsidiaries for the time period 2000-2010. The results show that agglomeration advantages, such as sectoral specialisation, a certain economic diversity as well as a region's economic and technological performance prove to be some of the most important pull factors for FDI in transition regions. In addition, the labour market factors prove to play an important role in the location of FDI.
Keywords: 330; Multinationales Unternehmen; Betriebliche Standortwahl; Diskrete Entscheidung; Agglomerationseffekt; Transformationsstaaten; Ostdeutschland; Polen; Tschechien